Pengaruh Pembiayaan Murabahah, Musyarakah dan Mudharabah terhadap Profitabilitas Bank Muamalat Indonesia Periode 2020-2023 - Defayana Putri, Anadila; Verlandes, Yuliasnita (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
This study is motivated by the importance of bank profitability (ROA) influenced by the financing provided. The Islamic banking industry in Indonesia has grown rapidly, particularly since the establishment of Bank Muamalat Indonesia (BMI) in 1992 as the first Islamic bank in Indonesia. This research aims to determine the effect of Murabahah, Musyarakah, and Mudharabah financing on the profitability of Bank Muamalat Indonesia during the period of 2020–2023. A descriptive quantitative approach is employed, using secondary data from Bank Muamalat's quarterly financial reports for 2020–2023, which were published on BMI's official website. The data analysis includes classical assumption tests, multiple linear regression analysis, T-test, F-test, and the coefficient of determination. The results of this study show that Murabahah financing has a significant partial effect on profitability (ROA) with a significance value of 0.021, while Musyarakah financing does not have a significant effect on profitability (ROA) with a significance value of 0.167. Mudharabah financing has a significant effect on profitability (ROA) with a significance value of 0.036. Furthermore, the analysis of Murabahah, Musyarakah, and Mudharabah financing shows that, simultaneously, these types of financing have a significant effect on profitability (ROA), as evidenced by a significance value of 0.011. The coefficient of determination test results indicate that Murabahah, Musyarakah, and Mudharabah financing contribute 59% to profitability (ROA), while the remaining 41% is influenced by other variables outside of this study.